O dispositivo do cancelamento nas redes sociais : entre os jogos de verdade e a moral na sociedade de controle - Oliveira, Dayane Adriana Teixeira (2024)
In today's society, with the advent of the internet and the popularization of social media, the power to speak out has become more democratic. At the same time, the devices for organizing and regulating discourse have become more decentralized, as hypervisibility exposes individuals to vulnerability, surveillance, and the judgment of others. In this context, one of the control devices that has emerged in the digital age is “cancel culture”. In recent years, this device, popularly known as cancel culture, has established itself on social media, promoting a kind of virtual ordeal in which individuals are exposed, judged, and punished for speeches and/or behaviors considered "morally" condemnable by other users of the networks. Thus, considering the regularity of this social phenomenon in cyberspace, this research aims to analyze how cancel culture constitutes a control device for the discourse and behavior of individuals, highlighting contemporary truths and morality in the society of control, where the function of surveillance and punishment is shared by social media users. The theoretical discussions that have led us to achieve these objectives are within the field of Foucauldian Discourse Studies, which allows us to think about the articulations between regimes of discourse and the production of truths and subjectivities in contemporary society. To do so, we mobilize the concepts of subject, discourse, power-knowledge relations, truth, device, and governmentality, which help us understand cancel culture as a set of discursive and non-discursive control practices that reveal power relations and knowledge that invoke divisions of subjects according to legitimacy parameters based on regimes of truth. In terms of methodology, we adopt what has been named as archaeo-genealogical, based on Foucauldian postulates that provide us with tools for analyzing the subject and statements. It is also important to consider the large amount of information circulating on the web. We are also interested in the singularities of the corpus that make up this archive, as these represent the escape routes of the device. Thus, we selected the cancellation case of volleyball player Maurício Souza, canceled on social media for a comment considered homophobic, and rapper Karol Conká, which occurred during her participation in the reality show Big Brother Brasil (BBB) in 2021 as the objects of study for this research. Through the analysis of this sample, we seek to understand not only the functioning of the device but also its escape routes and the moral and ethical issues that permeate it and enable the emergence of different subjectivities. In this way, we conduct our analyses in order to reveal, through the cancel culture device, the truth games in which individuals move to other subject positions. We also examine how this self-relationship reveals the way in which the individual asserts themselves as a subject of equality in the relationship with oneself and with others, causing them to shift to other subject positions (FOUCAULT, 2003b). The shift in subject position (former volleyball player — canceled — elected politician; and activist — canceled — uncanceled) attests to the rarity of events and highlights the power dynamics of the knowledge-power relationships that constitute the cancel culture device, the agency of the subjectivation processes it engenders, and the ruptures that fracture lines bring about.